Developing a load case for analysis of Squeak and Rattle events in passenger cars - Blom, Rasmus; Nilsson, Jonatan (My University, 2020)
A part of Volvo Cars strategy is shifting engineering activities to the early phases of the product development, without the need for complete vehicle prototypes. An important early phase activity in the product development of passenger cars is to evaluate Squeak & Rattle emitted from subsystems in the car. The subsystem studied in this project is the instrument panel (IP). Today’s excitation signals applied onto the IP is longer than necessary and not optimized for Squeak & Rattle evaluation. The aim of this thesis is consequently to develop effective excitation signals and provide the method of how this is achieved for further improvements and the possibility to develop new excitation signals for future product development of passenger cars. The thesis describes the process of recording excitation- and response signals, for the car as a whole and the IP subsystem. Nine different road tracks are recorded for two cars. A methodology for creating shortened excitation signals is explained, with crucial steps of identifying Squeak & Rattle events, grouping these into parts and concatenating them sequentially in time domain. The frequency content of the shortened excitation signals is examined to avoid significant deviations from the unshortened excitation signals. Eleven different concepts for the development of an excitation signal is created. The synthesized signals performance is verified with two test rigs. With regards to the Squeak & Rattle causing properties of the signal and the time compression ability, an optimal concept is presented. This concept proved to have favourable characteristics although further optimization could generate an even better concept. The methodology is not flawless, whilst nevertheless having the capability to compress the total excitation signal time by up to 95% and maintaining decent quality. Possible error sources and further methodology improvements is finally discussed.
Keywords: squeak, rattle, excitation signal, signal compression, product development; relative displacement, instrument panel, FFT, testing, accelerometers, CAE, optimization